Hands-on Activities to Foster the Use of English (2017)
ABSTRACT: This action research project focuses on the effects of using hands-on activities in a first grade of 34 students in a public elementary school. To find out students learning styles and multiple intelligences strategies visual and kinesthetic material was taken into account to support lessons following the topics of first grade syllabus. This study states the importance of including students’ interests, realities and needs in order to create an environment that invites them to use English at the same time they learn by doing. The findings suggest that kinesthetic activities and tactile and visual materials can be effective to improve learners’ linguistic skills.